Surface roughness of acrylic resins processed by microwave energy and polished by mechanical and chemical process - Célia M. Rizzatti-Barbosa; Morgana Nicoleti Gabriotti; Laís Regiane Silva-Concilio; Fabio A. Joia; Cristiane Machado; Margarete Cristiane Ribeiro (Universidade Estadual de Campinas, 2015)
The aim of this study was to evaluate the influence of polymerization methods (microwave energy - MW, and water bath - WB) and polishing techniques (chemical - C and mechanical - M) on the surface roughness of one heat-polymerized acylic resin (Vipi-Cril). Forty acrylic resin disk-shaped samples were made according to ADA specification nº 12. Half of samples were processed by microwave energy (500W for 3 minutes), and the other half by water bath (74±1 ºC for 9 hours). After deflasking, the samples were trimmed with a sequence of abrasive aluminum oxide sandpapers of different grades (180, 220 and 400) and divided in 4 groups according to polymerization methods and polishing techniques: G1: MW+CP, G2: MW+MP, G3: WB+CP and G4: WB+MP. Surface roughness values were measured using a Surfcorder SE 1700 rugosimeter (Kosaka Laboratory Ltd, Kosaka, Japan). Mann-Whitney test (p=.05) indicated significant differences between polishing methods processed by microwave energy (p= .0018), and between polishing methods processing by water bath (p= .0002). Samples processed by both methods (water bath or microwave energy) showed smoother surfaces when polished by mechanical polishing method, and polymerization methods did not influence in surface roughness.